The Old Testament for a complex world : how the Bible's dynamic testimony points to new life for the Church - Howard, Cameron B. R., 1980- (2021)
"Shows how the critical study of the Old Testament helps us understand the Bible as a dynamic testimony for our changing future"--
The Bible's dynamic witness -- Adapting popular culture -- Rethinking theological assumptions -- Developing a new genre -- Biblical foundations for creative change.
Includes bibliographical references (pages 127-131) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Language, style; Bible -- Evidences, authority, etc; Church renewal